Higher rates of neuropsychiatric adverse events leading to dolutegravir discontinuation in women and older patients. Issue 1 (10th November 2016) - Hoffmann, C; Welz, T; Sabranski, M; Kolb, M; Wolf, E; Stellbrink, H‐J; Wyen, C
Abstract : Objectives: Dolutegravir (DTG), a second‐generation integrase strand transfer inhibitor (INSTI), is now among the most frequently used antiretroviral agents. However, recent reports have raised concerns about potential neurotoxicity. Methods: We performed a retrospective analysis of a cohort of HIV‐infected patients who had initiated an INSTI in two large German out‐patient clinics between 2007 and 2016. We compared discontinuation rates because of adverse events (AEs) within 2 years of starting treatment with dolutegravir, raltegravir or elvitegravir/cobicistat. We also evaluated factors associated with dolutegravir discontinuation. Results: A total of 1950 INSTI‐based therapies were initiated in 1704 patients eligible for analysis within the observation period. The estimated rates of any AE and of neuropsychiatric AEs leading to discontinuation within 12 months were 7.6% and 5.6%, respectively, for dolutegravir ( n = 985), 7.6% and 0.7%, respectively, for elvitegravir ( n = 287), and 3.3% and 1.9%, respectively, for raltegravir ( n = 678). Neuropsychiatric AEs leading to dolutegravir discontinuation were observed more frequently in women [hazard ratio (HR) 2.64; 95% confidence interval (CI) 1.23–5.65; P = 0.012], in patients older than 60 years (HR: 2.86; 95% CI: 1.42–5.77; P = 0.003) and in human leucocyte antigen (HLA)‐B*5701‐negative patients who initiated abacavir at the same time (HR: 2.42; 95% CI: 1.38–4.24; P = 0.002). Conclusions: In this large cohort, the rate of discontinuation of dolutegravir because of neuropsychiatric adverse events was significantly higher than for other INSTIs, at almost 6% within 12 months. Despite the limitations of this retrospective study, the almost three‐fold higher discontinuation rates observed amongst women and older patients underscore the need for further investigation, especially in patient populations usually underrepresented in clinical trials.